Implementasi Metode Fuzzy Logic Untuk Monitoring Suhu dan Kelembaban Cahaya Pada Tanaman Bawang - Muhammad Khaerudin; Khabibillah (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2025)
Monitoring humidity, temperature, and light intensity has so far been done manually, using watering. In this study, a microclimate engineering system was created so that these environmental factors could be conditioned. This technological innovation, created with an internet-based automatic control system, is one of the applied technological innovations in agriculture that can be realized to create a microclimate within the demonstration garden. With the control mechanism implemented in the test room, which has the ability to monitor several indicators in real-time and monitor environmental factors that affect plant growth as needed. This research uses an automated control mechanism with fuzzy logic and IoT as the basic control for onion plants, replacing manual systems. This allows for plant growth to be supported by microclimate conditioning practices tailored to the needs of the plant, particularly onions